A near-complete genome assembly of Monochamus alternatus a major vector beetle of pinewood nematode - Longsheng Xing; Bo Liu; Dunyang Yu; Xuan Tang; Jianghua Sun; Bin Zhang (Scientific Data, 2024)
Abstract The Japanese sawyer beetle, Monochamus alternatus, is not only one of the most important wood boring pest itself, but also a major vector of the invasive pinewood nematode (PWN), which is the causal agent of the devastative pine wilt disease (PWD) and threats the global pine forest. Here, we present a near-complete genome of M. alternatus at the chromosome level. The assembled genome was 792.05 Mb with contig N50 length of 55.99 Mb, which is the largest N50 size among the sequenced Coleoptera insects currently. 99.57% of sequence was anchored onto ten pseudochromosomes (one X-chromosome and nine autosomes), and the final genome harbored only 13 gaps. BUSCO evaluation revealed the presence of 99.0% of complete core genes. Thus, our genome assembly represented the highest-contiguity genome assembly as well as high completeness in insects so far. We identified 20,471 protein-coding genes, of which 20,070 (98.04%) were functionally annotated. The genome assembly of M. alternatus provides a valuable resource for exploring the evolution of the symbiosis between PWN and the vector insects.